A Bibliometric Analysis of Fuzzy Logic Applications inIntelligent Systems - Oktavianing Putri, Muizzul Azizah; Dita Suci Yofana; suhartono (Jurnal Informatika dan Sains Media (JISMA), 2024)
This study aims to determine the mapping of research on trends in the application of Fuzzy Logic in intelligent systems using aquantitative approach in bibliometric studies with VOS Viewer. The data analysis technique used is mapping the results of VOS Viewerbibliometric visualization related to the application trends of Fuzzy Logic in intelligent systems based on the number of clusters andtopic items. The results of Network Visualization of Co-occurrence show that, based on VOS Viewer bibliometric study mapping, theresults of network visualization of Fuzzy Logic application trends in intelligent systems are divided into 8 clusters and 200 topic items.Meanwhile, based on Overlay Visualization and Density Visualization, the 2019-2024 period shows the center of attention on FuzzyLogic applications in fuzzy control and artificial intelligence, which reflects a significant increase in publications in this field, withmany studies that have been conducted by other researchers.